Entrepreneurship in Small and Medium Enterprises: A Catalyst for Capacity Building and Sustainable Youths Employment Generation in the Federal Capital Territory, Abuja, Nigeria - Duru, Innocent .U.; Anyanwu, Sarah .O. (International Journal of Social and Administrative Sciences, 2019)
This study investigated whether entrepreneurship in Small and Medium Enterprises (SMEs) can be a facilitator for capacity building and sustainable youth’s employment generation in the Federal Capital Territory, Abuja, Nigeria. The study used the survey research design. A structured questionnaire was employed for the collection of data. The views of 100 SMEs entrepreneur selected through the purposive sampling technique were elicited on whether entrepreneurship in SMEs can promote capacity building and sustainable youth’s employment generation in Abuja. The results showed that that entrepreneurship in SMEs can facilitate capacity building and sustain employment generation among youths in Abuja. However, the study revealed that entrepreneurship in SMEs can contribute effectively to the provision of capacity building and sustainable job for youths in Abuja. The finding revealed that access to finance was identified as the greatest barrier facing SMEs entrepreneur in the generation of sustainable employment for youths. Furthermore, the main channels through which SMEs entrepreneur create job for youths in the study area were becoming drivers of innovation and becoming the engine of economic growth. The results showed that entrepreneurship in SMEs is a catalyst for capacity building and sustainable youth’s employment generation in the Federal Capital Territory, Abuja. The study, therefore, recommends that: besides the microfinance banks, entrepreneurship development banks should be established with a view to providing fund to support SMEs and other enterprises in general and the government should provide the enabling environment for SMEs entrepreneur to thrive.